2011
DOI: 10.1089/lap.2011.0264
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Enucleation of Esophageal Gastrointestinal Stromal Tumor Using Prone Positioning in a Patient with Severe Chronic Obstructive Lung Disease

Abstract: Chronic obstructive lung disease (COPD) is a high-risk factor for pulmonary complications in esophageal surgery. We reported a case of esophageal gastrointestinal stromal tumor (GIST) in a patient with severe COPD. Upper gastrointestinal endoscopy and computed tomography revealed a 3×2-cm submucosal tumor at the lower esophagus, and positron emission tomography showed a hypermetabolic mass (SUV(max)=5.6). Forced expiratory volume in 1 second (FEV(1)) was 33.0% of predicted and FEV(1)/forced vital capacity rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1,2 The proposed advantages of the prone position are obtained for the following reasons: gravity will shift the cardiopulmonary organs toward the anterior chest wall with retracting the connecting esophagus from the vertebra, artificial pneumothorax by CO 2 gas compress the lung without manual retraction, and adequate artificial pneumothorax decreases the blood loss during the operation. 3 As the occurrence of submucosal tumor of the esophagus was rare, only few papers for thoracoscopic enucleation of esophageal submucosal leiomyomas and gastrointestinal stromal tumors using the prone position were reported [4][5][6][7][8] (Table 1). This paper presents 2 typical cases of esophageal submucosal tumors, leiomyoma, and schwannoma operated with the prone position, and this is the first report to propose the advantages of left thoracoscopic approach with the prone position for lower thoracic esophageal submucosal tumor resection.…”
mentioning
confidence: 99%
“…1,2 The proposed advantages of the prone position are obtained for the following reasons: gravity will shift the cardiopulmonary organs toward the anterior chest wall with retracting the connecting esophagus from the vertebra, artificial pneumothorax by CO 2 gas compress the lung without manual retraction, and adequate artificial pneumothorax decreases the blood loss during the operation. 3 As the occurrence of submucosal tumor of the esophagus was rare, only few papers for thoracoscopic enucleation of esophageal submucosal leiomyomas and gastrointestinal stromal tumors using the prone position were reported [4][5][6][7][8] (Table 1). This paper presents 2 typical cases of esophageal submucosal tumors, leiomyoma, and schwannoma operated with the prone position, and this is the first report to propose the advantages of left thoracoscopic approach with the prone position for lower thoracic esophageal submucosal tumor resection.…”
mentioning
confidence: 99%
“…This surgical approach has gained widespread acceptance not only for thoracic esophagectomy but also for enucleation of SMT originating from the thoracic esophagus. Yamada et al reported thoracoscopic enucleation of esophageal GIST using the prone position with excellent postoperative outcomes [ 11 ]. Jeon et al also demonstrated the safety and efficacy of video-assisted thoracic surgery for enucleation of esophageal submucosal tumors [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Despite the lack of a confining serosal surface in the esophagus, we find that enucleation without rupture of the tumor capsule is readily achievable. Several case reports 7,8,10,13 of successful E-GIST enucleation have been reported in patients being disease free on follow-up. Blum et al 6 reported a series of 4 E-GISTs and, contrary to our findings, found tumor enucleation to be difficult because of poor tumor coherence and a lack of a true capsule, leading them to recommend esophagectomy for all but the smallest lesions (<2 cm).…”
Section: Discussionmentioning
confidence: 99%